ECHOCARDIOGRAPHY MEASUREMENT OF PULMONARY HYPERTENSION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Some people with COPD develop pulmonary hypertension (PHT), which is a prevalent condition in and of itself. Its presence is linked to poorer clinical progression and shorter survival times. The purpose of this study was to use echocardiography to evaluate pulmonary hypertension (PHT) and right ventricular size in patients with chronic obstructive pulmonary disease (COPD) and to determine whether or not these variables were associated with disease severity. A total of sixty COPD patients were chosen from the medical ward of Al-Yarmouk Teaching Hospital. They were categorized according to the severity of their condition using the GOLD classification system. After that, they had echocardiography to assess the size of their right ventricle and the estimated systolic pressure of their pulmonary arteries. The results showed that out of the total number of patients, 20 (33.3%) had no PHT, 10 (16.7%) had mild PHT (ePPASP 36–45 mmHg), 21 (35.0%) had moderate PHT (ePPASP 46–60 mmHg), and 9 (15.0%) had severe PHT (ePPASP >60 mmHg). In moderate COPI, the frequency of PHT was 57.1%; in severe COPI, it was 65%; and in very severe COPI, it was 91.7%. Among the patients with IL, 18.3% had enlarged right ventricles. Hemodynamic alterations on the right side of the heart, including RV enlargement and PHT, are strongly associated with the severity of chronic obstructive pulmonary disease (COPD) as classified by GOLD. It is worthwhile to search for PHT in this cohort because it is frequently found in COPD patients.